New multifuncional divalent metal-coordinated sulfophosphonates: structures and proton conductivities - Bazaga-García, Montse; Pérez-Colodrero, Rosario Mercedes; Salcedo, Inés R.; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio; Demadis, Konstantinos D. (My University, 2021)
Metal phosphonate-based coordination polymers are structurally versatile multifunctional compounds that may contain a number of acidic groups such as P-OH; SO3H, COOH, N+-H…These features result in formation of extended H-bond networks and confer proton conducting properties. In this work, the crystal structures resulting from the combination of the amino-sulfophosphonate ligand (H2O3PCH2)2-N-(CH2)2-SO3H with different divalent metal ion, are reported. Optimal synthesis conditions were implemented by microwave methodology and high through-put screening. For cupper derivatives, single-crystal data were employed. While for Mn(II) derivative the crystal structure was solved ab initio from synchrotron X-ray powder diffraction data. The arrangement of the sulfonic groups determines a wide variety of metal-ligand coordination modes and the creation of efficient hydrogen bonding networks for proton transport, as has been observed for other lanthanide derivatives. For copper derivatives the presence of an auxiliary ligand (1,10-phenanthroline, 2,2’-bipyridine or 4,4’-bipyridine) were required to obtain a crystalline compound. As a consequence of this structural variability, different H bond networks can be generated leading to a wide range of proton conductivity values.
Keywords: Química - Congresos; Polímeros - Congresos; Coordination polymers; Sulfophosphonates; Proton-conductivity